(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Multiple sclerosis (MS) is a disease affecting the central nervous system (CNS), with inflammation and demyelination of nerves, eventually resulting in nerve damage and disabilities. The risk of developing MS enlarged by infectious mononucleosis, which is caused by delayed primary infection by Epstein-Barr Virus (EBV). Early reports consistently demonstrated an increased antibody response in MS patients versus healthy subjects towards different EBV antigens, including the EBV nuclear antigen-1 (EBNA-1). In Iraq, number of researchers found that the EBV have a possible role at some point in the course of the disease, others reported that the EBV pathogenesis have an important role in the triggering of MS disease. Objective: To compare the sero-prevalence of EBV nuclear antigen-1 antibody (EBNA-1 IgG) among the Iraqi MS patients and controls and find out whether there is a relation between disease severity and EBNA-1 IgG titer. Methods: This case-control study conducted on 120 MS patients aged between 13-42 years, and 120 apparently healthy age- and sex-matched volunteers as controls. Three ml of whole blood were collected from all MS patients and controls and put in gel tubes. The blood samples were centrifuged at 5000 RPM for 5 minutes to get serum from the gel tubes. Serum was preserved in (-20ºC), and then used for enzyme-linked immunosorbent assay (ELISA). The ELISA study was performed using ELISAs kits (Abnova /Taiwan) for EBNA-1 IgG antibodies measurement. Results: EBNA-1 IgG was positive in 51.7% (62/120) of MS patients and 39.2% (47/120) of controls, (P=0.035). The median of EBNA-1 IgG level of MS patients and controls were 81.08 U/ml, and 67.73 U/ml, respectively (P=0.043). And EBNA-1IgG was significantly higher in younger age groups. Patients with the first-line and second-line treatment showed no significant differences in EBNA-1 IgG levels, while the median level in patients without treatment (newly diagnosed) and those who were at early years of the disease was higher. Conclusion: EBNA-1 antibody could play a triggering role in MS because it is significantly higher in MS patients than in controls, especially at younger age groups, early stages of the disease and in female patients. Keywords: Multiple sclerosis, EBV, EBNA-1 IgG, ELISA Citation: Ali ZA, Al-Obaidi AB, Almashta SA. The potential role of Epstein-Barr Virus Nuclear Antigen-1 (EBNA-1) in multiple sclerosis. Iraqi JMS. 2022; 20(1): 3-10. doi: 10.22578/IJMS.20.1.2